2022
DOI: 10.3390/buildings12050516
|View full text |Cite
|
Sign up to set email alerts
|

Resilient City: Characterization, Challenges and Outlooks

Abstract: The increasingly severe environmental pollution and the Earth’s ecological crisis make the concept of resilient cities (RCs) a hot topic in urban research. We ran a bibliometric analysis to analyze the research progress, areas, hotspots, and strategies pertaining to RCs. The core collection came from the Web of Science (WoS) database as the data source to explore 4462 literature works on RCs. The results revealed that development time series analysis is divided into three stages. Changes in the number of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Content analysis, on the other hand, is a qualitative research method that involves the systematic examination of textual data to identify patterns, themes, and trends, as outlined by Ren et al [35]. This approach can be applied to analyze the content of articles, abstracts, and titles to comprehend the research focus in a specific field, as demonstrated in the studies by Scotti Requena et al [36] and Wu et al [37].…”
Section: Methodsmentioning
confidence: 99%
“…Content analysis, on the other hand, is a qualitative research method that involves the systematic examination of textual data to identify patterns, themes, and trends, as outlined by Ren et al [35]. This approach can be applied to analyze the content of articles, abstracts, and titles to comprehend the research focus in a specific field, as demonstrated in the studies by Scotti Requena et al [36] and Wu et al [37].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, resilience emphasizes the development of flexibility and adaptability in critical engineering and infrastructure systems in order to maintain minimal functionality during crises, and to recover as quickly as possible afterwards. The introduction of this concept has led to a shift in the critical infrastructure industry, moving from an attitude of simply protecting critical infrastructure to actively improving its resilience [19,20].…”
Section: Engineering Resiliencementioning
confidence: 99%
“…Cooperative networks between the different regions have been initially established. The author cooperation map shows the publishing status of studies in related research fields, identifying authors with strong research capacities and highlighting the collaboration of increasingly significant and engaged researchers [29]. For the purpose of creating an author cooperation map, the software node type is set as "Author" and the time slice as one year (Figure 3).…”
Section: Annual Journal Publicationsmentioning
confidence: 99%